2014
DOI: 10.1002/term.1952
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cultures of mouse submandibular and parotid glands: a comparative study

Abstract: Freshly isolated salivary cells can be plated on an extracellular matrix, such as growth factor-reduced Matrigel (GFR-MG), to induce the formation of three-dimensional (3D) structures. Cells grown on GFR-MG are able to form round structures with hollow lumina, capable of sustaining amylase expression. In contrast, cells grown on plastic do not exhibit these features. Our recent studies have used mouse parotid gland (PG) cells, grown on different extracellular matrices, as a model for acinar formation. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
6
14
0
Order By: Relevance
“…8). These results are consistent with those from previous reports (Larsen et al, 2010;Leith et al, 2014;Melnick & Jaskoll, 2000;Redman, 1988;Riberiro et al, 2006), with slight differences in the timing of some of the details (Larsen et al, 2010;Leith et al, 2014;Ogawa et al, 2013;Okumura et al, 2012;Rego et al, 2016;Tucker, 2007). Of all the major salivary glands, the sublingual salivary gland is the first to form and development is already complete at birth (Chi, 1996;Poulsen et al, 1986;Redman, 1988).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…8). These results are consistent with those from previous reports (Larsen et al, 2010;Leith et al, 2014;Melnick & Jaskoll, 2000;Redman, 1988;Riberiro et al, 2006), with slight differences in the timing of some of the details (Larsen et al, 2010;Leith et al, 2014;Ogawa et al, 2013;Okumura et al, 2012;Rego et al, 2016;Tucker, 2007). Of all the major salivary glands, the sublingual salivary gland is the first to form and development is already complete at birth (Chi, 1996;Poulsen et al, 1986;Redman, 1988).…”
Section: Discussionsupporting
confidence: 92%
“…This is different from the other major salivary glands. It is thought that complete formation of the parotid salivary gland is associated with the production and accumulation of secretory proteins in the acini at the final stage of postnatal development (Denny et al, 1997;Lawson, 1972;Leith et al, 2014;Redman & Sreebny, 1970). Important genetic changes can be observed during this period, which are consistent with the above results (Denny et al, 1997;Poulsen et al, 1986).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Several recent studies have demonstrated that TJs can be formed from primary salivary in vitro, 110,[116][117][118][119] an advance which can be used to study barrier function of the salivary epithelium in a system that more closely resembles native tissue. Furthermore, the use of knockout mice for the various TJ proteins will also prove useful in determining the role of these proteins for in vivo salivary gland functioning.…”
Section: Models Available To Study Tight Junctions In Salivary Glandsmentioning
confidence: 99%